Innovation and entrepreneurial networks in Europe - Fernandez Perez, Paloma , 1964-; Rose, Mary B. (Routledge international studies in business history, 2010)
Analyzes innovation in entrepreneurship networks from a European perspective. This book combines themes of entrepreneurship, innovation and networks with a specifically European focus, highlighting the wide variations at the national, regional and business level